2019
DOI: 10.1111/tbed.13142
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of haemagglutinin gene deciphering a new genetically distinct lineage of canine distemper virus circulating among domestic dogs in India

Abstract: Summary Canine distemper (CD) is one of the highly contagious and invariably fatal viral diseases of dogs and other carnivores. Despite the widespread use of modified live vaccines to control CD, the prevalence of disease has increased at an alarming rate in recent years. Although a number of factors may be ascribed for vaccine failure, antigenic differences among the vaccine and wild‐type strains have gained the interest of researchers. Considering the high genetic variability of haemagglutinin gene (H gene) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…As previously reported the H gene region is highly variable with more number of amino acid variations (Martella et al, 2006;Sarute et al, 2013). Of all the reported amino acid variations in this study, we noticed that D530G was previously reported and was consistently reported in four isolates here (Bhatt et al, 2019).…”
Section: Partial H Gene Of CDV Is Highly Variablesupporting
confidence: 79%
See 3 more Smart Citations
“…As previously reported the H gene region is highly variable with more number of amino acid variations (Martella et al, 2006;Sarute et al, 2013). Of all the reported amino acid variations in this study, we noticed that D530G was previously reported and was consistently reported in four isolates here (Bhatt et al, 2019).…”
Section: Partial H Gene Of CDV Is Highly Variablesupporting
confidence: 79%
“…All the eight isolates show distant relationship with vaccine strains (America-1) and other isolates from the NCBI database (Fig 4). However, the previous reports suggested that the Indian isolates were grouped either under European lineage (Swati et al, 2015;Ashmi et al, 2017) or Asia-5/ India-1 (Bhatt et al, 2019). Our findings suggest some CDV strains circulating in India were evolving from South America-2 or Asia-4.…”
Section: Molecular Epidemiology Of CDVmentioning
confidence: 42%
See 2 more Smart Citations
“…This scenario may result in the adaptation of CDV to be able to infect different hosts. Due to the global distribution of the CDV, phylogenetic genotyping of this virus has been based on the H gene sequence and segregated it into several major clades: America-1, America-2, Asia-1, Asia-2, Africa-1, Africa-2, European wildlife, Arctic, and Europe-1/SouthAmerica-1 [6], while the latest clades have recently been described as America-3 to -5, Asia-3 to -5, South America-2, and South America-3 [23,24]. In addition, the Caspian clade was recently isolated as the cause of a mass die-off of Caspian seals since 1988 [25].…”
Section: Introductionmentioning
confidence: 99%